Accounting Information Security Control and Satisfaction of Accountants Regarding Accounting Information Systems - Vuong Thi Thanh Nhan; Nguyen Ngoc Khanh Dung; Tran Phuoc (Ital Publication, 2023)
This study analyzes the factors affecting accountants’ satisfaction with the accounting information system in Vietnamese enterprises. The research results of this study show that the factors affecting user satisfaction with the accounting information system are directly influenced by four factors: the quality of the accounting workforce, perception of usefulness, system quality, and information quality. The quality of the accounting workforce is the factor that has the greatest direct impact on the accountant’s satisfaction. The second is the perceived usefulness factor. The third is the system quality factor, and the last is the information quality factor. In particular, the results of this study indicate that humans are an important factor. Knowledge of accounting information security control is directly proportional to accountants’ satisfaction with the accounting information system. The results can be used to recommend enterprises improve accountants’ satisfaction, helping to increase work efficiency. Objectives: The main objectives of this study include: (1) Identifying the factors influencing the satisfaction of accountants with the accounting information system in enterprises in Vietnam. (2) Determining the relationship between accounting information security and the satisfaction of accountants with the accounting information system. (3) Providing recommendations to enhance the satisfaction of accountants with the accounting information system in enterprises in Vietnam. Methods: This study uses qualitative and quantitative research. During the qualitative process, this study analyzed related works. Group discussions are used to provide initial assessments of measurement scales, concepts, and research hypotheses and to adjust, supplement, and explore influencing factors. The questionnaire and the research model are reviewed by the experts. Quantitative research involved data collection through survey investigations based on a designed questionnaire via Google Forms. The formal research survey was conducted using a stratified sampling method, encompassing businesses from various sectors. The quantitative research employed the Cronbach Alpha reliability test for the measurement scales, exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and the use of structural equation modeling (SEM) to assess the structural relationships. Descriptive statistics and tests of significance were also utilized. Findings: The results of the study on the factors affecting user satisfaction with an accounting information system are directly influenced by four factors: system quality, information quality, quality of accountants, and perceived usefulness. The quality of the accounting workforce has the greatest direct impact on the accountant’s satisfaction, followed by perceived usefulness, system quality, and information quality factors. Novelty:This study discovered a relationship between knowledge of accounting information security and the level of satisfaction among accountants regarding information technology systems in enterprises in Vietnam. This finding can assist enterprises in implementing strategies to provide more training on accounting information security for their employees. Doi: 10.28991/ESJ-2023-07-05-06 Full Text: PDF